The Frenkel Method in Physiotherapy cerebellar syndromes (Cuestiones de Fisioterapia, 2005)
This article come the method of the professor Heinrich Sebastian Frenkel. This Swiss neurologist, not very well-known, it was the first in introducing the concept of exercise in order to restore the dexterity and to improve ambulation in the rehabilitation of the patients with cerebellar diseases, specially. Frengel's method consists of to carry out some series of exercises ordered of minor to more difficulty actively. The most difficult exercises are the more complexes as for neuromuscular coordination, and not those that they require more effort. It is worked in decubitus, sitting and standing (exercises of coordination, of march and of balance)